FANDOM


$ a = b $
$ a^2 = ab $
$ a^2 - b^2 = ab - b^2 $
$ (a - b)(a + b) = b(a - b) $
(a - b)(a + b) = b(a - b)
$ (a + b) = b $

$ but\ a = b $
$ therefore: $

$ a + a = a $
$ 2a = a $

$ hence $

$ 2 = 1 $

However, this results in dividing by $ 0 $, because $ a - b = a - a = 0 $


EDIT:

Your mistake comes in step 5, when you divided by (x-y) on both sides. 
Since x = y, x-y = 0, so you are dividing by zero, which is undefined 
(illegal!). 

Source: http://mathforum.org/library/drmath/view/55792.html